Assessment of pollution load from industrial activities of Nghi Son Economic Zone (Thanh Hoa province) - Thu Trang, Cao Thi; Ngoc, Dinh Hai; Thao, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2020)
Thanh Hoa coastal waters have received a large amount of waste from industrial activities of Nghi Son Economic Zone such as thermal power, vegetable oil production, wood processing, steel rolling and petroleum refinery. Employing environmental rapid assessment method, the discharged industrial wastewater from Nghi Son Economic Zone was calculated. The pollution load includes organic matter (13 thousand tons), total nitrogen - TN (27.4 thousand tons), total phosphorous - TP (967.8 tons), total suspended solid - TSS (12.3 thousand tons). In addition, wastewater also contained phenol, oil and grease, cyanide, sulfites, heavy metals (Fe, Zn, Cr). If this wastewater is not treated, the amount of pollutant discharged to Thanh Hoa coastal area will be much greater and impact on sensitive ecosystems.